Kebutuhan Kalori Pekerja di Perusahaan Kontraktor Alat Berat - Rizky Maharja; Fira Ananda; Ade Wira Lisrianti Latief; Rusda Ananda; Achmad Mawardi Shabir; La Ode Hidayat (Nutrition Science and Health Research, 2023)
Background: The increase in work productivity is one of the goals of the implementation of Occupational Safety and Health (K3) in the workplace which can be done through occupational nutrition. l: This study aimed to calculate the employees’ calorie needs. Method: This was categorized as a descriptive study. The sampling was done using the total sampling, totaling 41 people. The calorie needs were obtained from the daily nutritional requirement by age, gender, and physical workload. The physical workload was observed and aligned with the Indonesian National Standard No. 7269: 2009 concerning the Assessment of Workload based on the Level of Calorie Needs according to Energy Expenditure. The data were analyzed descriptively. Result: The findings showed that all male employees and the majority of employees aged around 18-19 years old (young adults) had a normal BMI and heavy workload. The respondents mostly had calorie needs of 1,221 Kcal. Conclusion: The employees’ calorie needs in this heavy construction equipment company are varied. The average calorie need of the employees working in this company is 1,221 Kcal with the lowest calorie of 940 Kcal, while the highest is 1,767 Kcal